Academic education system as an object of sociological study - Volnistaya, Marina G. (Journal of the Belarusian State University. Sociology, 2023)
In this article the object of sociological study is academic systems of higher education institutions in Belarus. The author applies the methodology of general systems theory and social systems theory. The factors of academic systems transformation in the conditions of global institutional changes of higher school architectonics are researched. The author identifies the peculiarities of the processes of academic transformation occurring under the influence of digitalisation, massification and commercialisation of higher education. The author investigates the perception of academic anomalies by the academic community of higher education as a result of transformations and institutional changes in education. The empirical basis for the sociological study includes the results of the national expert survey conducted among the academic community of Belarusian higher education institutions. The research involved higher school teachers, leading specialists and heads of the structural divisions of metropolitan and regional higher education institutions.
Keywords: social systems theory; academic education system; academic quality; nature of academic systems; academic education; academic community; academic culture; academic communication; academic values; academic anomalies